The Olympic effect: A reply - Wolfgang Maennig; Felix Richter (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2011)
Rose & Spiegel (2011) find that Olympic Games host countries experience significant positive and lasting effects on exports. They interpret their results as an indication that countries use the hosting of such an event as a signal of their (new) openness and competitiveness. We challenge these empirical findings on the grounds that the comparison of structurally different and non-matching groups might suffer from a selection bias. We demonstrate that with an appropriately applied matching and treatment methodology, the significant Olympic export effect disappears.
More recent version: http://hdl.handle.net/10419/93228
Keywords: L83; 330; export; Olympic Games; international trade; treatment; Sportveranstaltung; Wirkungsanalyse; Export; Internationale Wirtschaft; Bias